The model of Proboscis Monkey welfare in Indonesian Safari Park (Taman Safari Indonesia) using Five Domain Animal Welfare - Imtiyaaz, Cassytta Dhiya; Alikodra, Hadi Sukadi; Manansang, Jansen; Trihastuti, Yohana; Darusman, Huda Shalahudi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The proboscis monkey (Nasalis larvatus) is endemic to Borneo and is currently categorized as Endangered on the IUCN Red List. Not all proboscis monkeys can be conserved effectively in natural habitats. Zoos are ex-situ conservation, which aims to support conservation and ensure the welfare of animals. This research uses the Five Domain method to examine the welfare of proboscis monkeys at Taman Safari Indonesia (TSI) Bogor. The research was carried out from October 2022 to March 2023. The proboscis monkeys at TSI consumed feed ravenously, as indicated by the high percentage of ingestive behavior, 34.24%. Based on the MCU (medical check-up) results through interviews with veterinarians, the proboscis monkeys at TSI are in good health. No abnormal behavior was found in proboscis monkeys at TSI. Natural behavior and high use of environmental enrichment can be indicators of good welfare. Overall, proboscis monkeys at TSI show good welfare and management. The proboscis monkey welfare model can support ex-situ link in situ synergy as a sustainable conservation strategy. The condition of proboscis monkeys at TSI is in the welfare category based on behavioral observations and comprehensive studies.